2017
DOI: 10.1007/s40120-017-0081-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Imaginative Distention Therapy to Cope with Fatigue. DIMMI SI Study: The First Randomized Controlled Trial in Multiple Sclerosis

Abstract: IntroductionFatigue is a frequent, disabling, and difficult to treat symptom in neurological disease and in other stress-related conditions; Integrated Imaginative Distention (IID) is a therapy combining muscular and imaginative relaxation, feasible also in disabled subjects; the DIMMI SI trial was planned to evaluate IID efficacy on fatigue.MethodsThe design was a parallel, randomised 1:1 (intervention:waiting list), controlled, open-label trial. Participants were persons with multiple sclerosis (pwMS), perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Limited information was provided about the intervention evaluated in Nazari, Shahreza, Shaygannejad, and Valiani (2015), it consisted of twice weekly relaxation sessions of 40 minutes over 4 weeks. In Sgoifo et al (2017), participants received Jacobsen relaxation exercises biweekly over the course of 8 weeks, with sessions lasting between 40 and 60 minutes delivered by one psychotherapist. At the end of treatment, 4% attrition was observed in the treatment group.…”
Section: Sensitivity: Internalmentioning
confidence: 99%
“…Limited information was provided about the intervention evaluated in Nazari, Shahreza, Shaygannejad, and Valiani (2015), it consisted of twice weekly relaxation sessions of 40 minutes over 4 weeks. In Sgoifo et al (2017), participants received Jacobsen relaxation exercises biweekly over the course of 8 weeks, with sessions lasting between 40 and 60 minutes delivered by one psychotherapist. At the end of treatment, 4% attrition was observed in the treatment group.…”
Section: Sensitivity: Internalmentioning
confidence: 99%
“…Sajadi et al’s 69 RCT reported a significant difference in sleep quality between the group that participated in foot reflexology and the placebo group following the intervention; however, the intervention group’s average PSQI score was significantly worse than the control group’s PSQI score at baseline. Sgoifo et al’s 34 RCT reported no significant difference in ISI change scores between the integrative imaginative distention intervention group and the waitlist control group. In Jensen et al’s pilot RCT, 64 participants received an intervention with neurofeedback and hypnosis (NF-HYP), mindfulness and hypnosis (MM-HYP), or hypnosis alone (control).…”
Section: Resultsmentioning
confidence: 97%
“…39,51,57 Sleep was stated as the primary outcome in nine 26,27,32,36,41,43,45,46,50 of the 37 studies. The Pittsburg Sleep Quality Index (PSQI) was the most commonly used sleep outcome utilized in 19 26,29-31,35-39,41,42,44,48,50,53-55,57,60 of the studies followed by the Insomnia Severity Index (ISI) (n=10 32-34,37,39,42,44,45,56,62 ), actigraphy (n=5 37,38,43,46,60 ), and sleep log/diary data (n=5 38,43,46,56,57 ); six of the studies incorporated an objective measurement (actigraphy (n=5 38,43,46,56,57 ); EEG (n=1 45 )). Interventions included physical activity (n=13 31-33,37-39,41,45,46,50,51,53,55 ), CBT-I (n=6 42-44,56,57,62 ), CBT/psychotherapy (n=4 26,27,30, ), mindfulness/relaxation (n=6 28,48,49,58-60 ), education and self-management support (n=3 29,36,54,61 ), and complementary and alternative interventions including acupuncture 47 , neurofeedback and hypnosis 64 , trauma releasing exercises 52 , foot reflexology 35 , integrated imaginative distention 34 (all ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations